Diagnosis of an imported Plasmodium ovale wallikeri infection in Malaysia. (December 2016) - Liew, Jonathan; Mahmud, Rohela; Tan, Lian; Lau, Yee
Abstract Plasmodium ovale is rare and not exactly known to be autochthonous in Malaysia. There are two distinct forms of the parasite, namelyP. ovale curtisi (classic form) andP. ovale wallikeri (variant form). Here, the first sequence confirmed case of an importedP. ovale wallikeri infection in Malaysia is presented. Microscopy foundPlasmodium parasites with morphology similar toP. ovale orPlasmodium vivax in the blood films. Further confirmation using polymerase chain reaction (PCR) targeting the small-subunit rRNA gene of the parasite was unsuccessful. Genus-specific PCR was then performed and the product was sequenced and analysed. Sequence analyses confirmed the aetiological agent asP. ovale wallikeri . New species-specific primers (rOVA1v and rOVA2v) were employed andP. ovale wallikeri was finally confirmed. The findings highlight the need to look out for imported malaria infections in Malaysia and the importance of a constantly updated and validated diagnostic technique.